Amorphous K‐Buserite Microspheres for High‐Performance Aqueous Zn‐Ion Batteries and Hybrid Supercapacitors - Zhi‐Qiang Wang; Hong‐Ming Chen; Xiao‐Dong Liu; Li‐Ying Song; Bu‐Sheng Zhang; Yun‐Guo Yang; Zhao‐Cheng Zhang; Qian Li; Tian‐Qi Gao; Jing Bai; Woon‐Ming Lau; Dan Zhou (Advanced Science, 2023)
Abstract Aqueous Zn‐ion batteries (AZIBs) and Zn‐ion hybrid supercapacitors (AZHSCs) are considered promising energy‐storage alternatives to Li‐ion batteries due to the attractive merits of low‐price and high‐safety. However, the lack of suitable cathode materials always hinders their large‐scale application. Herein, amorphous K‐buserite microspheres (denoted as K‐MnOx) are reported as cathode materials for both AZIBs and AZHSCs, and the energy‐storage mechanism is systematically revealed. It is found that K‐MnOx is composed of rich amorphous K‐buserite units, which can irreversibly be transformed into amorphous Zn‐buserite units in the first discharge cycle. Innovatively, the transformed Zn‐buserite acts as active materials in the following cycles and is highly active/stable for fast Zn‐diffusion and superhigh pseudocapacitance, enabling the achievement of high‐efficiency energy storage. In the AZIBs, K‐MnOx delivers 306 mAh g−1 after 100 cycles at 0.1 A g−1 with 102% capacity retention, while in the AZHSCs, it shows 515.0/116.0 F g−1 at 0.15/20.0 A g−1 with 92.9% capacitance retention at 5.0 A g−1 after 20 000 cycles. Besides, the power/energy density of AZHSCs device can reach up to 16.94 kW kg−1 (at 20 A g−1)/206.7 Wh kg−1 (at 0.15 A g−1). This work may provide some references for designing next‐generation aqueous energy‐storage devices with high energy/power density.